Balancing Act: Examining the Efficacy of Environmental Protection Laws in Natural Resource Management - Fauzan Saputro (Universitas Muhammadiyah Surakarta, 2024)
This abstract explores the intricate interplay between environmental protection laws and their effectiveness in the realm of natural resource management. Termed a